Sustaining Social Tolerance Through the Principles of Religious Moderation in a Pluralistic Society: A Study on the Religious Moderation Village in Sedanau Subdistrict - Hariswati Rachmadani Putri (Universitas Nasional, 2025)
The Religious Moderation Village in Sedanau Subdistrict serves as a concrete representation of the government’s and community’s efforts to preserve tolerance within a diverse society. This study aims to analyze how the values of religious moderation such as tolerance, national commitment, non-violence, and accommodation of local culture are applied in the social life of a pluralistic community to maintain harmony, as well as the challenges and strategies involved in sustaining cohesion. The research employs a descriptive qualitative approach with data collection techniques consisting of interviews, observations, and document studies. The findings indicate that the implementation of religious moderation values including national commitment, tolerance, non-violence, and accommodation of local culture has successfully minimized conflict and fostered social harmony. However, challenges such as religious exclusivism and limited religious literacy still require attention. This study recommends strengthening interfaith education, increasing youth involvement, and institutionalizing routine interreligious dialogue. Keywords: Religious Moderation, Tolerance, Plural Society, Harmony, Sedanau